Determination of root dentin and cementum micro hardness - Fabiano Ribeiro Cirano; Giuseppe Alexandre Romito; José Hildebrando Todescan (Universidade Estadual de Campinas, 2015)
Vickers micro hardness was assessed on root dentin and cementum in 30 canines obtained from the Periodontics Discipline tooth bank. Crown and cervical portion of the root were discarded by a transverse section situated 3mm, apically, from the cemento-enamel junction on the buccal surface, thus obtaining the root specimen. On root dentin, mean micro hardness values were obtained for 3 regions: (DR1) from 0.05 to 0.1 mm of the cemento dentin junction - 30.64 VHN; (DR2) from 0.3 to 0.5 mm of the cemento dentin junction - 56.92 VHN and (DR3) from 0.8 to 1.0 mm of the cemento dentin junction - 32.70 VHN. After statistical analysis (Variance Analysis test, p < 0,05), we conclude that micro hardness at the DR2 region was statistically greater than that at the DR3 region which was, in turn, greater than that at the DR1 region. The mean micro hardness of cementum was 19.70 VHN.